Telaah Etnografis Ritual Mandi Safar: dari Tradisi Diskursif, Dialog Interreligius, hingga Rekonsiliasi Pasca-Konflik - Kholid, Mohammad Ridho; Kholid, Mohammad Fikri Nugraha; Arizandy, Aan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The Safar-Bath Ritual (Ritual Mandi Safar) is an annual event regularly held by both Muslim and Hindu communities particularly in South Lampung. This ritual is a means of self-sanctification from calamities, dangers and diseases in which it is believed God has dropped down those in the Safar month (the second month of Islamic callender). However, as a tradition, it is alive and preseved in one hand, but it is also considered as the deviant practice against with Islamic teaching on the other hand. Unlike such teological suspicion, this study aims to challenge the Safar- Bath Ritual by putting it as a discursive tradition which is enlivened by both communities as the way of act and behave to respond nature phenomena. This study employs a qualitative method by collecting data through observations, interviews, and gathering relevant resources. This study reveals that by treating the Safar-Bath Ritual as the discursive tradition it can bridge inter-religious dialogue between Muslim and Hindu who often involve in horizontal conflicts. It is also able to openly pave an alternative way for post-conflict reconciliation of both communities.